Effects of the hammock method on preterm newborns: systematic review and meta-analysis - Amanda Gomes de Sousa; Etiene Etiene FarahFarah Teixeira Carvalho; João Marcos Feliciano de Souza; Juliana Fernandes Barreto Mendonça; Cristiane Aparecida Moran; Évelim Leal de Freitas Dantas Gomes (Zaslavsky O.Yu., 2021)
Premature birth is caused by a diversity of factors and leads to respiratory, heart, motor, and metabolic disorders due to the immaturity of body organs. The proper positioning of a premature newborn is a highly beneficial non-pharmacological intervention. The hammock method is based on synactive theory and leads to improvements in physiological variables, behavioral organization, and the harmonization of movements. The aim of the present systematic review and meta-analysis was to evaluate the effects of the hammock method on vital signs, pain/stress, and behavioral state of preterm newborns. A search was performed for clinical trials that compared the hammock method to other techniques in preterm newborns. This review was conducted following the PRISMA guidelines and only included articles reporting clinical and quasi-experimental trials conducted in the neonatal intensive care unit with preterm newborns using the Hammock method as the main intervention. Eight articles composed the qualitative analysis and four of these articles composed the meta-analysis. The hammock method proved to be viable and promising for the reduction in pain/stress as well as improvements in the behavioral state of preterm newborns.